Increasing the Effectiveness of the System by Supply chain management on The Basis of the System-Assessment Mechanism - Jaafar Naser Abdulridha; Alaa Ammar Talib Al-Hamdawee (International Journal of Supply Chain Management, 2020)
Abstract— This article is devoted to the development of one of directions of optimization of the system of quality supply chain management in modern enterprise-self-assessment mechanism. In the work of organized approaches to classification by quality costs a new category